1997
DOI: 10.3109/17518429709167364
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cerebral palsy with botulinum toxin A: Functional benefit and reduction of disability. Three case reports

Abstract: Three patients with cerebral palsy are described suffering, respectively, of pes equinus, spasm of the m. teres major and flexion spasm of the hand, who were treated with botulinum toxin A. These patients demonstrate not only the local reduction of the muscular hyperactivity following treatment with botulinum toxin A but also the potential functional benefit resulting from such a treatment. Thus, local intramuscular injection of botulinum toxin A in children with cerebral palsy should be considered as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Table II regroups, under these four main outcomes of interest, participants in the included studies who were GMFCS levels IV and V and who showed a positive effect from the intervention. Reduction in muscle tone and improvements in ranges of motion were also shown in several studies (Table SII) 20,25–28,30,32–34,36,39 …”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Table II regroups, under these four main outcomes of interest, participants in the included studies who were GMFCS levels IV and V and who showed a positive effect from the intervention. Reduction in muscle tone and improvements in ranges of motion were also shown in several studies (Table SII) 20,25–28,30,32–34,36,39 …”
Section: Resultsmentioning
confidence: 58%
“…Three studies 21,27,28 reported positive results of BoNT‐A treatment in increasing ease of positioning but with no statistical analysis of the results ( n =10 in total; Tables II and SII). BoNT‐A was shown to result in a statistically significant increase in ease of care in two studies 34,37 ( n =18 in total) and also in another three studies 27,28,33 without any statistical analysis ( n =4 in total; Tables II and SII). In three studies, 25,35,36 participants in GMCFS levels IV and V showed an improvement in the GMFCS level ( n =30/54 in total) although statistical analysis was either not performed or performed on a mixed population in these studies (Table SII).…”
Section: Resultsmentioning
confidence: 96%
“…The flexor pollicis brevis, opponens pollicis, adductor pollicis, and flexor pollicis longus were also chosen to be injected for the management of thumb spasticity. The triceps brachii, pectoralis muscles,19 teres major,24 and deltoid12 were injected in a few cases due to shoulder deformity.…”
Section: Resultsmentioning
confidence: 99%
“…Injury to the CNS that involves the cortico-reticulobulbo-spinal pathway results in altered muscle tone and reduced activity of the musculoskeletal system, which has repercussions for functional capacity 5,[13][14][15][16][17] . The leading cause of neurological dysfunction in the adult population is CVA 27 , which results in a number of incapacitating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Spasticity is defined as a velocity-dependent increase in the resistance of muscles to passive movement, as well as by muscle weakness, pronounced hyperreflexia, abnormal cutaneous and autonomic reflexes with the Babinski sign, caused by lesion of the upper motor neuron involving the cortico-reticulo-bulbo-spinal pathway 4,[7][8][9][10][11][12][13][14] . Since it affects the musculoskeletal system, the consequences of spasticity has a direct effect, albeit in varying degrees of severity, on the lives of patients, impairing their ability to carry out activities of daily living, as well as causing pain, contractions and deformities, all of which hinder the rehabilitation process [15][16][17][18][19] . Functional activity, or functionality, is defined as the ability to carry out activities of daily living such as feeding oneself, remaining mobile, making transfers, maintaining personal hygiene and locomoting 20 .…”
mentioning
confidence: 99%